Analisis Kesuksesan Sistem Informasi Manajemen Puskesmas (SIMPUS) Menggunakan Metode Delone and Mclean di UPT Puskesmas Sananwetan Kota Blitar - Cornelia Justicia Viana; Erna Selviyanti; Atma Deharja; Andri Permana Wicaksono (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2024)
Implementation of SIMPUS at the UPT Puskesmas Sananwetan Blitar has a several problems were found, including that there were still patient data that had not been filled in, the loading process was long, and an analysis had never been carried out to assess the success of the system. The purpose of this study was to analyze the successful use of SIMPUS at Public Health Center Sananwetan Blitar based on the relationship between system quality, information quality, service quality, intention to use, user satisfaction, and net benefit through the information system success analysis method Delone and Mclean (2003). This type of research is quantitative with data collection techniques through questionnaires. The sample for this research was 55 officers who had a username and password to log in to SIMPUS. The results of this research are that the significance value for all variables is <0.05 and is positive so that the relationship between each variable is in the same direction towards the user and user satisfaction. The strongest relationship is in the quality of service to user satisfaction with a correlation coefficient of 0.646 and a coefficient of determination of 41.73%. The lowest relationship occurs in system quality to user intensity with a correlation coefficient of 0.429 and a coefficient of determination of 18.40%.